Caveolin-1 Phosphorylation Is Essential for Axonal Growth of Human Neurons Derived From iPSCs - Wang, Shanshan; Zhang, Zheng; Almenar-Queralt, Angels; Leem, Joseph; DerMardirossian, Celine; Roth, David M.; Patel, Piyush M.; Patel, Hemal H.; Head, Brian P. (Frontiers in Cellular Neuroscience, 2019)
Proper axonal growth and guidance is essential for neuron differentiation and development. Abnormal neuronal development due to genetic or epigenetic influences can contribute to neurological and mental disorders such as Down syndrome, Rett syndrome and autism. Identification of the molecular targets that promote proper neuronal growth and differentiation may restore structural and functional neuroplasticity and thus improve functional performance in neurodevelopmental disorders. Using differentiated human neuronal progenitor cells (NPCs) derived from induced pluripotent stem cells (iPSCs), the present study demonstrated that, in early stages differentiation of human NPCs, neuron-targeted overexpression constitutively active Rac1 (Rac1CA) and constitutively active Cdc42 (Cdc42CA) enhance expression of P-Cav-1, T-Cav-1 and P-cofilin and increases axonal growth. Similarly, neuron-targeted over-expression of Cav-1 (termed SynCav1) also increases axonal development by increased axon length and volume. Moreover, inhibition of Cav-1(Y14A) phosphorylation blunts Rac1/Cdc42-mediated axonal growth and differentiation of human NPCs, and SynCav1(Y14A)-treated NPCs exhibited blunted axonal growth. These results suggest that: 1) P-Cav-1 is necessary for proper axonal growth during early stages of neuronal differentiation, 2) SynCav1-mediated axonal growth is dependent upon Cav-1 phosphorylation, 3) Rac1/Cdc42CA-mediated neuronal growth may in part be dependent upon P-Cav-1. In conclusion, Cav-1 phosphorylation is essential for axonal growth during early stage of human neuronal differentiation.